BENDEL KESLINGMAS NO 122TAHUN 2014 - Hani, Desita Frida, Nirma Dedi, Dkk (Buletin Keslingmas, 2014)
RSUD  Prof.  Dr.  Margono  Soekarjo  Purwokerto  is  the  regional  hospital type  B  area  that  provide  specialized  medical  care  and  subspecialty  limited. Pavilion Soeparjo Rustam treatment room is a treatment that treating all kinds of  diseases both infectious diseases and non-infectious diseases, so the potential occurrence of nosocomial infection. The purpose of this study was to determine of  disinfection  effectiveness  in  reducing  the  number  of  germs  air  in  Paviliun Soeparjo  Rustam  treatment  room  RSUD  Prof.  Dr.  Margono  Soekarjo Purwokerto.   This research is analytic research with cross sectional approach. Type of  variable  used  is  the free  variable (disinfection),  dependent  variable  (number  of  air  germs),  potentially  confounding  variables  (temperature,  humidity,  lighting, ventilation and a vast volume of space).    According to the result of investigation, the average number of germs air  before  disinfection  is  265  CFU/m3,  after  disinfection  is  20  CFU/m3.  Average  effective  disinfection  is  92.45%.  The  average  temperature  was  23.5  oC.  The average  humidity  was  50.55  %.  The  average  lighting  is  179.7  Lux.  Extensive ventilation in Paviliun Soeparjo Rustam treatment room is 0.9 m2. Room volume is 36 m3.   Researchers concluded the use of disinfection is effective in reducing the number  of  air  germs.  The  researcher  gives  suggestion  if  another  researcher wants to do a disinfectant they must using full PPE.